Merchants : the community that shaped England's trade and empire, 1550-1650 - Smith, Edmond (Yale University Press, 2021)
In the century following Elizabeth I's rise to the throne, English trade blossomed as thousands of merchants launched ventures across the globe. Through the efforts of these 'mere merchants,' England developed from a peripheral power on the fringes of Europe to a country at the center of a global commercial web, with interests stretching from Virginia to Ahmadabad and Arkhangelsk to Benin. Edmond Smith traces the lives of English merchants from their earliest steps into business to the heights of their successes. Smith unpicks their behaviour, relationships, and experiences, from exporting wool to Russia, importing exotic luxuries from India, and building plantations in America.
Also issued in print: 2021.
Keywords: Merchants -- Great Britain -- History -- 16th century.; Merchants -- Great Britain -- History -- 17th century.; Great Britain -- Commerce -- History -- 16th century.; Great Britain -- Commerce -- History -- 17th century.